2012
DOI: 10.1007/s11249-012-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion of Pulsed Plasma-Nitrided CoCrMo Implant Alloy

Abstract: In the present study, a forged CoCrMo (ISO 5832-12) has been subjected to pulsed plasma treatment in a N 2 /H 2 atmosphere at low temperatures (below 500°C). This treatment resulted in the formation of a layer composed by dispersed chromium nitride particles in a N-enriched metal matrix. The materials were tested for corrosion and tribocorrosion performance in 0.9 wt% NaCl at room temperature under controlled electrochemical conditions. After the treatment, the alloy loses its passive nature. The electrode pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
(44 reference statements)
1
25
1
Order By: Relevance
“…(9) this results in an increase of wear accelerated corrosion and thus of wear, an effect indeed observed in practice [2]. As another example, non passive alloys (passivation charge q¼0) should perform better under tribocorrosion conditions, as evidenced by the improved tribocorrosion behaviour of nitrided CoCrMo alloys reported by Bazzoni et al [85].…”
Section: Wear Accelerated Corrosionmentioning
confidence: 84%
See 1 more Smart Citation
“…(9) this results in an increase of wear accelerated corrosion and thus of wear, an effect indeed observed in practice [2]. As another example, non passive alloys (passivation charge q¼0) should perform better under tribocorrosion conditions, as evidenced by the improved tribocorrosion behaviour of nitrided CoCrMo alloys reported by Bazzoni et al [85].…”
Section: Wear Accelerated Corrosionmentioning
confidence: 84%
“…4 (0-0.3 V corresponds well with the threshold potential of 0.15 V [84] at which passive film thickening accelerates significantly. Recently, Espallargas et al [85] investigated the corrosion and tribocorrosion behaviour of a pulse plasma nitrided biomedical CoCrMo alloy. They observed that CoCrMo samples containing nitrogen in solid solution exhibit neither a passive behaviour nor a potential dependent transition to high wear.…”
Section: Effect Of Potential On Wearmentioning
confidence: 99%
“…The cell was equipped with a saturated calomel reference electrode, a graphite auxiliary electrode and a holder leaving only the one side of the specimen exposed to the corroding medium. In all cases the electrolyte volume was 800 ml and the sample surface which was in contact with the testing solution 1 cm 2 . The open circuit potential or corrosion potential E corr was recorded after 30 min stabilization whereas rapid (50 V/ h) and slow scan rates (0.6 V/h) were used.…”
Section: Corrosion Testsmentioning
confidence: 99%
“…However, their wear and corrosion stability are of great concern during the last years [1][2][3]. Literature studies showed that the released of metal ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have also been made in recent years to improve the tribological, corrosion, and tribocorrosion properties of biomedical alloys by surface engineering, mainly by applying an innovative surface coating [14][15][16] and by surface alloying [17][18][19]. In particular, the potential of S-phase coating and CrN coating to improve tribocorrosion behavior of biomedical alloys has been studied in details [20,21].…”
Section: Introductionmentioning
confidence: 99%